A systematic review of research on integration of ontologies with the model-driven approach. (17th May 2010) - Valiente, Maria-Cruz
Despite years of research, dealing with software complexity is still considered to be a challenging problem in Software Engineering. Software development is a complex process which requires the creation and management of a great deal of artefacts. In this vein, Model-Driven Engineering (MDE) has become a reference approach in software development. This paper presents a systematic review of the literature related to the integration of ontologies into the MDE approach. The objective of this paper is to provide an unbiased and up-to-date framework that helps software engineering researchers to identify new research activities and take advantage of this integration.